Cross-Cultural Perspectives on Psychological Research Practices and Opportunities: Do We All Have the (Same) Chance? - Boskovic, Irena; Perera, Nisali; Otgaar, Henry (Psychological Research on Urban Society, 2025)
The dominance of "WEIRD" (Western, Educated, Industrialized, Rich, and Democratic) authors might indicate significant differences in research practices between them and non-WEIRD researchers or highlight issues such as inequality and publishing bias. In this survey, using a convenience sample of researchers worldwide (N = 72), we examined current research practices and researchers' views on the feasibility of advancements in employed methodologies among and between researchers in both WEIRD and Non-WEIRD countries. Our results showed that research practices are fairly uniform across cultures, by researchers commonly relying on (student) convenience samples, using statistical packages such as SPSS and R, utilizing low-cost equipment, publishing once to five times a year, and contributing as reviewers and journal editors. Only significant differences were observed between WEIRD and Non-WEIRD researchers related to institutional support, such as opportunities for statistical consultancy and funding prospects. Respondents were supportive regarding progress in research practices, but cautioned that further developments might exacerbate existing inequalities, particularly at smaller and less funded institutions. Our main conclusion is that the visibility and outreach gap between WEIRD and non WEIRD researchers is primarily caused by systemic issues, rather than due to differences in research practices.